Effects of Music and Time of Day on Physiological Responses and Fatigue during Indoor Cycling: Pengaruh Musik dan Waktu terhadap Respons Fisiologis dan Kelelahan selama Bersepeda di dalam Ruangan - Halim, Stefanny; Sarvia, Elty (Universitas Muhammadiyah Sidoarjo, 2025)
Cycling has health benefits, but factors such as timing and music can affect performance and fatigue levels. There is still debate about the optimal time for cycling and the effects of music on endurance and perceived fatigue. In addition, the physiological responses of men and women to cycling have not been studied. This study used four indoor cycling scenarios, namely: (1) morning–without music, (2) morning–with music, (3) afternoon–with music, and (4) afternoon–without music. The objectives of this study were to analyze the effects of time and music on physiological responses, evaluate differences in fatigue between men and women, and assess the correlation between energy (Ecost) and heart rate while cycling. The parameters observed included heart rate, blood pressure, fatigue level (IFRC), and heart rate variability (%CVL). The results showed that the four scenarios did not produce significantdifferences in heart rate, blood pressure, route completion time, or fatigue levels. Blood pressure after activity tended to be higher in men, while heart rate was higher in women. The %CVL classification showed that most respondents were in the “non-urgent improvement” category (women 57.14%; men 78.57%). IFRC scores also showed that most respondents were at a moderate level of fatigue. Spearman's rank test confirmed a very strong correlation between Ecost and heart rate in all scenarios, both in men and women. These findings provide an overview of physiological responses and fatigue in indoor cycling under different time and music conditions.